2006
DOI: 10.1086/501058
|View full text |Cite
|
Sign up to set email alerts
|

Ruminal Fermentation and Fill Change with Season in an Arctic Grazer: Responses to Hyperphagia and Hypophagia in Muskoxen (Ovibos moschatus)

Abstract: We studied castrated adult muskoxen fed a standard diet of grass hay and supplement throughout the year to determine seasonal changes in digesta passage, fill, and fermentation without the confounding effects of reproductive demands or changes in food quality. Although food intake increased by 74% between spring and autumn, mean retention times of fluid and particulate digesta markers were maintained between seasons in both the rumen (9-13 h) and the intestines (27-37 h). The rumen contained 84.5% of digesta a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 73 publications
5
44
2
Order By: Relevance
“…Domestic cattle-a convenient model for large grazers-actually have a shorter fluid retention time in the forestomach than the large browsers moose, giraffe, and okapi-indicating that the larger omasum in cattle might indeed be an adaptation to a higher fluid throughput in this species (Clauss et al, 2006b). Given the similarities in forestomach fluid retention between cattle and other large grazers such as water buffalo (Bubalus bubalis) (Bartocci et al, 1997), American bison (Bison bison) (Towne et al, 1988), or muskoxen (Ovibos moschatus) (Barboza et al, 2006), we hypothesize that the strategy of high fluid throughput is common in many grazing ruminants (for a potential adaptive function, see Clauss et al, 2006b); as fluid outflow from the rumen is positively correlated with saliva secretion in cattle (Cassida and Stokes, 1986;Maekawa et al, 2002b), it appears probable that grazers achieve this strategy by a high production of saliva from their comparatively smaller salivary glands. Robbins et al (1995) observed a difference in salivary consistency, with the browser mule deer showing a much more viscous saliva than the domestic, grazing ruminants.…”
Section: Functional Significancementioning
confidence: 99%
“…Domestic cattle-a convenient model for large grazers-actually have a shorter fluid retention time in the forestomach than the large browsers moose, giraffe, and okapi-indicating that the larger omasum in cattle might indeed be an adaptation to a higher fluid throughput in this species (Clauss et al, 2006b). Given the similarities in forestomach fluid retention between cattle and other large grazers such as water buffalo (Bubalus bubalis) (Bartocci et al, 1997), American bison (Bison bison) (Towne et al, 1988), or muskoxen (Ovibos moschatus) (Barboza et al, 2006), we hypothesize that the strategy of high fluid throughput is common in many grazing ruminants (for a potential adaptive function, see Clauss et al, 2006b); as fluid outflow from the rumen is positively correlated with saliva secretion in cattle (Cassida and Stokes, 1986;Maekawa et al, 2002b), it appears probable that grazers achieve this strategy by a high production of saliva from their comparatively smaller salivary glands. Robbins et al (1995) observed a difference in salivary consistency, with the browser mule deer showing a much more viscous saliva than the domestic, grazing ruminants.…”
Section: Functional Significancementioning
confidence: 99%
“…The rumen and reticulum influence food intake because these organs have the greatest capacity and are where most fermentation takes place in the gastrointestinal tract of ruminants (Clauss et al 2003; Barboza et al 2006;Ramzinski and Weckerly 2007). The contents within the rumen-reticulum consist of forage water, forage particles, and animal fluid (Van Soest 1994); the weight of all three constituents is digesta load.…”
Section: Introductionmentioning
confidence: 99%
“…The contents within the rumen-reticulum consist of forage water, forage particles, and animal fluid (Van Soest 1994); the weight of all three constituents is digesta load. The digesta load fluctuates with the rate of fermentation and food intake, as well as with the nutrient content and fraction of liquid in the selected diet (Jenks et al 1994; Barboza et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the movement behaviour of muskox cows that died to those that lived during the study period did not yield indications of changes in movement behaviour that could be linked to the fate of the individual, because of the large variation in movement behaviour among individuals. High forage intake in summer and autumn also aids preparing the essential rumen microflora for the upcoming period of hypophagia (Barboza et al 2006), and rumen microbes are dramatically suppressed by starvation (Aagnes et al 1995). Thus, the surprisingly high level of activity and likely foraging observed in this study, even in midwinter, may reflect the need for some energy acquisition as well as the need for sustaining a functional rumen microflora throughout the snow-covered period until fresh plant material is accessible again.…”
Section: Resultsmentioning
confidence: 99%
“…The consistent, forward moving foraging behaviour of the muskoxen throughout the day and 'night' in summer, and the presence of foraging bouts outside the summer season intercepted by fast, directional movements are consistent with the expected patchy distribution of resources outside the summer season. Indeed, muskox food intake increases markedly from spring to autumn, which ensures sufficient fat depots before the lean period (Barboza et al 2006). Not being able to replenish the fat reserves may result in low pregnancy rates, loss of foetus, and ultimately the death of the cow.…”
Section: Resultsmentioning
confidence: 99%